NORMATIVE STUDY ON THE WAIVING OF MANAGEMENT RIGHT OF THE PROVINCIAL GOVERNMENT OF WEST NUSA TENGGARA WITHIN THE DEVELOPMENT OF THE MANDALIKA RESORT AREA - Swasta, Putu Juni (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The research aims to study the regulations on the waiving of Management Right of the Provincial Government of West Nusa Tenggara within the Mandalika Resort area and its legal consequences. This is a normative research because it is analyzing regulations which relate to the waiving of management right. It applies statutory, conceptual and case approach. It also uses primary, secondary and tertiary legal materials. To collect legal materials, it employs literature study and furthermore is organized descriptively and analyzed qualitatively. This research finds out that the waiving right is a deliberate termination of a possession and tenure right of property by a subject right with specific purposes. Procedures and requirements stipulated by the Provincial Government of West Nusa Tenggara under the Government Regulation, and the Regulation of Agrarian Minister/Head of National Land Body No 9 of 1999. In the Law of National Land, the right waiving associated with the acquisition of the land right, either for business purposes or public interest, can be carried out in the following ways: transfer of right, waiving of right and revocation of right. Keywords: the Management Right, the Waiving of Right